Analisis Kualitas Air di Sungai Cimanuk Kecamatan Jatibarang Dan Pemanfaatannya - Muhammad Arfan Al-Ghozi Prasetyo; Muhammad Fajar Arzena (Majalah Ilmiah UNIKOM, 2023)
Sungai Cimanuk Water Quality Assessment Based on the Standards Set by Governor Regulation No. 38 of 1991 and Government Regulation No. 82/2001.An evaluation of the water quality of the Cimanuk River was conducted based on the quality standards established by Governor Regulation No. 38 of 1991 and Government Regulation No. 82/2001. The evaluation results indicate that the water in the Cimanuk River meets the quality standards of Class B, C, and D as stipulated in Governor Regulation No. 38 of 1991 at several upstream points. However, elevated levels of substances such as manganese, zinc, and detergents exceeding permissible limits were detected at specific locations. Furthermore, according to the criteria outlined in Government Regulation No. 82/2001, the water quality in the Cimanuk River reaches Class I during the rainy season but deteriorates to Class III and IV during the dry season. The primary conclusion drawn from this evaluation is that the water quality in the Cimanuk River does not consistently meet the standards set by both Governor Regulation No. 38/1991 and Government Regulation No. 82/2001, indicating a significant discrepancy in the assessment of water quality in this river. Key Words: quality assessment , water quality, water pollution